DYNAMIC SUN PROTECTION STRUCTURES FOR HOT-DRY CLIMATE CONDITIONS - Ahmadov Tolibjon.Akmalovich (Web of Journals Publishing, 2025)
Protecting buildings from excessive solar radiation in hot and dry climates is one of the main factors in increasing energy efficiency and ensuring indoor comfort. Dynamic sunshield structures play an important role in this process, as they are able to operate in accordance with environmental conditions and help maintain the indoor temperature of the building at an optimal level. This article analyzes the types of dynamic sunshield systems suitable for this climate zone, their operating principles, materials used and their efficiency. The results of the study can be useful in developing energy-efficient and environmentally friendly construction solutions.
Keywords: Sunshield, dynamic structures, hot and dry climate, energy efficiency, ecological construction, thermal comfort, solar radiation, innovative facade systems.